Development of an all-fiber broadband source using supercontinuum generation (2025)
In this research work, the design, characterization and implementation of a broadband source (denoted as $S_H$) using the nonlinear phenomenon of supercontinuum (SC) generation were carried out. This source consists of a ring laser cavity for generating ultrashort pulses using an erbium-doped fiber laser (EDFL), a bidirectional erbium-doped fiber amplifier (EDFA), and a 40 cm highly nonlinear fiber (HNLF). Characterization of the EDFL provided insights into the behavior of the cavity's output variables during transition from continuous wave to mode-locking (ML) regimes, with the latter representing 0.6\% of all possible polarization states. This enabled the determination of the effective gain window for the pulsed regime associated with output polarization states ($PS$) with azimuth and ellipticity of $ \psi = (147.8 \pm 1.6)^{\circ}$ and $ \chi=(-11.1 \pm 3.1)^{\circ}$, respectively, indicating that the generated vector solitons would have similar Stokes parameters. Additionally, it was found that in these ML regimes, unpolarized light ($P_U$) increased by 1.5 dB compared to polarized light ($P_{Pol}$), with an mean polarization degree ($DP$) of $(96.1 \pm 0.9)\%$. Subsequently, these pulses were seeded into the EDFA+HNLF system for SC generation. The characterization of the spectral broadening ($\Lambda_{S}$) dynamics showed nonlinear behavior as a function of the EDFA pump power, resulting in a shortening of the output pulse width of $S_H$ to about $120 ~{\rm fs}$, with a marked tendency towards linear polarization. The results also indicated that $\Lambda_{S}$ is highly dependent on the input polarization state to the HNLF, implying that a larger $\Lambda_{S}$ corresponds to a higher amount of $P_U$ and lower $DP$. This fact was used to find SC states that optimized $DP$ and $P_{Pol}$ by identifying regions with a $P_{Pol}> P_{U}$ ratio, achieving SC with $ 560 ~{\rm nm}$ of $\Lambda_{S}$, $52.6\%$ of $DP$, $ 3 ~{\rm dB}$ of $P_{Pol}/ P_{U}$, and $PS$ with $\psi =(-45.0 \pm 0.9) ^{\circ}$ of azimuth and $\chi = (5.1 \pm 0.7) ^{\circ}$ of ellipticity. Finally, the $S_H$ source configured with a 53\% DP was used to determine the absorption bands of organic solvents such as acetone and isopropanol through infrared (IR) transmission spectroscopy in the spectral range of $1-5 ~{\rm \mu m}$. The $S_H$ source enabled the characterization of absorption bands of functional groups in the mid-IR region, finding high absorption intensity of the methyl group and combination bands between CH and CO stretching modes, unlike a commercial SC source with $24\% $ DP used for comparison. Additionally, using the measured overtones for CH, CC, and OH in the near-IR region, the dissociation energies of these bonds were estimated, showing the potential of the $S_H$ source in spectroscopic characterization. \\ The results of this research demonstrated that the designed $S_H$ source can optimize parameters such as $DP$, $P_{Pol>U}$, and $\Lambda_{S}$ according to the type of application for which the source is used.